2015
DOI: 10.1021/acs.jpcb.5b03689
|View full text |Cite
|
Sign up to set email alerts
|

Forced Phase Separation by Laser-Heated Gold Nanoparticles in Thermoresponsive Aqueous PNIPAM Polymer Solutions

Abstract: We have investigated the formation, growth, and dissolution dynamics of aggregates of the thermoresponsive polymer poly(N-isopropylacrylamide) (PNIPAM) that form around laser heated gold nanoparticles (GNPs). The aggregates show an initial rapid growth followed by a slow long-term tail that is caused by the temperature dependent induction time until phase separation sets in. The maximum aggregate radius is determined by the distance from the GNP where the temperature crosses the binodal. Melting and evaporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…22,23 Orlishausen and Köhler identified two opposite regions formed in the laser-heated region: one is the expanded region of the solution because of the positive Soret coefficient, promoting the stretching of the molecules, and the other is the contraction region because of the aggregation of molecules to the phase-separated region. 24…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Orlishausen and Köhler identified two opposite regions formed in the laser-heated region: one is the expanded region of the solution because of the positive Soret coefficient, promoting the stretching of the molecules, and the other is the contraction region because of the aggregation of molecules to the phase-separated region. 24…”
Section: Introductionmentioning
confidence: 99%
“…Such a possibility has been tested for PNIPAM very recently. Under a brightfield optical microscope, Orlishausen and Köhler observed the dynamic growth of PNIPAM aggregates that formed around laser-heated Au NPs . The heating of 250 nm diameter Au NPs settled on a window in a 8–9 wt % PNIPAM solution with focused laser illumination at a constant power 51.9 mW (50–100 mW μm –2 or 5 × 10 6 –10 7 W cm –2 ) and wavelength 532 nm which enabled the growth of phase-separated aggregates with diameters of ∼10 μm at 0.3 s to ∼100 μm at 500 s. Note here that the ranges of these laser powers well exceed the threshold of vapor bubble generation around a Au NP. After laser heating was stopped, the aggregates dissolved from the outside.…”
Section: Introductionmentioning
confidence: 99%
“…Potential involvement of thermophoresis (thermodiffusion or Soret effect), which is a movement of molecules following the temperature gradient, was examined here as a mechanism of accumulation. It has been shown that the Soret effect leads to a distinct phase separation during the spinodal decomposition of a locally heated UCST (upper critical solution temperature) polymer blend and that laser heating of a near-critical mixture leads to long-lasting patterns. , Also, the formation of a transient concentration cage around laser-heated Au NPs due to the Soret effect has been studied, and the formation of a transient network of a thermoresponsive polymer around a heated Au NP has been reported . Given the temperature gradient, thermophobic molecules with a positive Soret coefficient ( S T > 0) move to the cold area whereas thermophilic molecules with a negative Soret coefficient ( S T < 0) move to the hot area. The Soret coefficient, S T , usually has a positive sign in water .…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Also, the formation of a transient concentration cage around laserheated Au NPs due to the Soret effect has been studied, 35 and the formation of a transient network of a thermoresponsive polymer around a heated Au NP has been reported. 36 Given the temperature gradient, thermophobic molecules with a positive Soret coefficient (S T > 0) move to the cold area whereas thermophilic molecules with a negative Soret coefficient (S T < 0) move to the hot area. 37−39 The Soret coefficient, S T , usually has a positive sign in water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%